Elevated nocturnal desaturation index predicts mortality in interstitial lung disease - Corte, T.J.; Wort, S.J.; Macdonald, et al., P.M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: Nocturnal desaturation may contribute to long-term pulmonary vascular stress in interstitial lung disease (ILD).We study the prevalence, severity and prognostic utility of nocturnal desaturation across ILD.Methods: ILD patients with overnight oximetry ( June 2006-August 2008) were reviewed (n=134). Significant nocturnal desaturation was considered as ≥10% of sleep with SpO2≤90%. Desaturation index (DI) was defined as the number of desaturation events >4%/hr. Covariates, including indices of nocturnal desaturation, were evaluated against mortality. Results: Nocturnal desaturation was present in 49 (37%) patients. 31% of patients had pulmonary hypertension (PH) on echocardiography. Increased DI was associated with higher mortality independent of age, gender and BMI (HR 1.04; 95% CI 1.00, 1.06; p=0.009). In separate models, DI and a) elevated brain natriuretic peptide (BNP; HR 1.04; 95% CI 1.00, 1.08; p=0.04); b) moderate-severe PH on echocardiography (HR 3.15; 95% CI 1.24, 8.00; p=0.02); and c) daytime resting SpO2 (HR 0.92; 95% CI 0.85, 0.99; p=0.04) independently predicted mortality following adjustment for age, gender and BMI. Conclusion: Nocturnal desaturation is common and may be severe in ILD. Elevated nocturnal DI predicts higher mortality across ILD, independent of other vascular parameters. This finding may have important implications for the pathogenesis of PH in IPF.